r-Learning services for elementary school students with a teaching assistant robot - Han, Jeonghye; Kim, Dongho (2009 4th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2009)
The r-Learning paradigm with educational robots is emerging as a part of e-Learning, which means using technology for learning. This study on using robots as a teaching assistant robot opened the possibility of r-Learning for English in classroom. We found that children like robot services for personal relationship in class and teachers prefer them related to their convenience to manage the lesson. Related robot services such as praising and cheering up or calling the roll are the effective way for motivating children to learn, enhancing the relationship between TIRO and children. We are going on conducting further field trials for new scenarios and services that motivate children and make them concentrate on class with teachers, pre-teachers, children, parents, robotic researchers, social scientists, etc.